The Relationship Between The Internal Marketing and Quality Services : a Filed Study on Samples of Customers and Employees In Iraqi Commercial Banks - بدراوي عبد الرضا فرج; موسى رافت عواد (Journal of Economics and Administrative Sciences, 2013)
Abstract The Paper highlights on one of the main activities in marketing management. That is the internal marketing in the commercial banks and its relationship with the quality services offered to satisfy customers needs and wishes in order to reach he ultimate objectives of those banks. Two state and five private banks in Basrah city (Iraq) were taken in a field study. The survey covered the opinions of (184) state bank employees and (158) clients . The analysis of the survey shows that there is a strong relationship between the internal marketing ( in the banks covered by the survey) and the quality of banking objective services and the private banks show greater interest and concern to the internal marketing than state banks. The paper also presents a number of important conclusions such as ; it is necessary to pay more attention to meet the satisfactions of state bank employees, offer training opportunities , assist them to overcome problems might they face and provide a good working environment . It is also recommended that internal marketing and its measures should be produced in the form of a code of practice.